Gold Price Forecasts in a Dynamic Model Averaging Framework – Have the Determinants Changed Over Time? - Dirk G. Baur; Joscha Beckmann; Robert Czudaj (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
The price of gold is influenced by a wide range of local and global factors such as commodity prices, interest rates, inflation expectations, exchange rate changes and stock market volatility among others. Hence, forecasting the price of gold is a notoriously difficult task and the main problem a researcher faces is to select the relevant regressors at each point in time. This combination of model and parameter uncertainty is explicitly accounted for by Dynamic Model Averaging which allows both the forecasting model and the coefficients to change over time. Based on this framework, we systematically evaluate a large set of possible gold price determinants and use both the predictive likelihood and the mean squared error as a measure of the forecasting performance. We carefully assess which predictors are relevant for forecasting at different points in time through the posterior probability. Our findings show that (1) DMA improves forecasts compared to other frameworks and (2) provides clear evidence for the time-variation of gold price predictors. – – Der Goldpreis wird durch eine breite Palette von lokalen und globalen Faktoren wie Rohstoffpreisen, Zinssätzen, Inflationserwartungen, Wechselkursänderungen und Aktienmarktvolatilität beeinflusst. Daher ist es eine schwierige Aufgabe den Goldpreis zu prognostizieren. Das Hauptproblem besteht darin, die relevanten Regressoren zu jedem Zeitpunkt auszuwählen. Diese Kombination aus Modell- und Parameterunsicherheit wird in unserem Dynamic Modell Averaging (DMA) Ansatz berücksichtigt, in dem sich sowohl das Prognosemodell als auch deren Koeffizienten im Laufe der Zeit ändern können. Basierend darauf untersuchen wir eine große Bandbreite möglicher Goldpreisdeterminanten hinsichtlich ihrer Vorhersagekraft und nutzen dabei sowohl die Predictive Likelihood als auch den mittleren quadratischen Fehler als Maß für die Vorhersageleistung. Wir analysieren anhand der a posteriori-Wahrscheinlichkeit, welche Prädiktoren zu verschiedenen Zeitpunkten für die Prognose relevant waren. Unsere Ergebnisse zeigen, dass (1) DMA die Prognose im Vergleich zu anderen Verfahren verbessert und (2) dass die Goldpreisprädiktoren sich über die Zeit verändert haben.
Keywords: C32; G10; G15; F37; 330; Bayesian econometrics; dynamic model averaging; forecasting; gold